2019
DOI: 10.1371/journal.pone.0226477
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of VISION Max automated cross-matching in comparison with manual cross-matching: A multidimensional analysis

Abstract: BackgroundVISION Max (Ortho-Clinical Diagnostics, Raritan, NJ, USA) is a newly introduced automated blood bank system. Cross-matching (XM) is an important test confirming safety by simulating reaction between packed Red Blood Cells (RBCs) and patient blood in vitro before transfusion. We assessed the benefits of VISION Max automated XM (A-XM) in comparison with those of manual XM (M-XM) by using multidimensional analysis (cost-effectiveness and quality improvement).Materials and methodsIn a total of 327 tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Automated analyzers have been introduced in hematology laboratories and blood bank laboratories; however, few studies have focused on laboratory efficiency in these laboratories with high manual workload [ 24 - 26 ]. These studies demonstrated the usefulness and applicability of FMEA in clinical laboratories and showed that automated methods are associated with lower RPNs than manual methods, which is in line with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Automated analyzers have been introduced in hematology laboratories and blood bank laboratories; however, few studies have focused on laboratory efficiency in these laboratories with high manual workload [ 24 - 26 ]. These studies demonstrated the usefulness and applicability of FMEA in clinical laboratories and showed that automated methods are associated with lower RPNs than manual methods, which is in line with the present results.…”
Section: Discussionmentioning
confidence: 99%
“… 26 The process of blood processing, including automatic activities such as group typing, subgroup typing, antibody screening, cross-matching, results entry, results reporting, and sending screening results from the laboratory to the blood bank, is yet to be fully automated. 18 , 19 , 26 , 28 , 29 , 32 , 34 , 35 , 39 The process of blood storage is commonly discussed in the literature, especially the automation of controlling the availability of blood units, checking the site of storage, and controlling the temperature of refrigerators. 26 , 35 The process of blood transfusion automation has also been discussed in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…The process of blood processing, including automatic activities such as group typing, subgroup typing, antibody screening, cross-matching, results entry, results reporting, and sending screening results from the laboratory to the blood bank, is yet to be fully automated. 18 , 19 , 26 , 28 , 29 , 32 , 34 , 35 , 39 …”
Section: Methodsmentioning
confidence: 99%
“…Based on user informed criteria for the development of ORTHO VISION® (VISION) and ORTHO VISION® Max Analyzers (Ortho Clinical Diagnostics, Raritan, NJ, US), fully automated systems for immunohematology testing, an opportunity to apply key attributes common to these instruments to a semi-automated solution was explored [4]. Using this concept ultimately provided a solution for those who wanted as many of the features of full automation in a semi-automated system.…”
Section: Introductionmentioning
confidence: 99%